Development of Teaching Materials Growth of Motion Learning Development Based on Android Applications - Alan Alfiansyah Putra Karo Karo; Ika Endah Puspita Sari; Dimas Arif Hidayat; Benny Aprial M; Liliana Puspa Sari (UNIB Press, 2021)
The purpose of this research is the development of teaching materials for motion learning based on android applications. ADDIE is a research model that researchers choose, namely analysis, design, development, implementation and evaluation. The results of the research as a whole are feasible by material experts and media experts on the components of content, language presentation, and graphics, it is obtained that an average percentage of 81.5% has very high criteria. Based on the overall assessment of the ease of using the product, the difficulty of understanding the material, and the difficulty of doing the questions, the average percentage is 84% in the very feasible category. The development of teaching materials for the development of motion learning development based on android applications is the result of this research. Based on the results of the study, it can be concluded that the product developed is considered very feasible.